PENGARUH TINGKAT PENDIDIKAN TERHADAP KUALITAS KERJA KARYAWAN PADA BANK PERKREDITAN RAKYAT "POLATAMA KUSUMA" KECAMATAN JIWAN KABUPATEN MADIUN - Ekik Mayundarwati (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
This study aims to determine  the level of employee education BPR POLATAMA KUSUMA  Madiun,  to determine  the quality  of employees  BPR POLATAMA KUSUMA Madiun,  and to determine  how much  influence  the level of education  of the employees' quality  of rural  banks "POLATAMA  KUSUM<\"  Madiun.  Determination   of the sample in this study using a sample  that is saturated  all employees  Rural Bank Polatama  Kusuma Madiun  totaling  50 employees.  Data collection  using questionnaires   and documentation. In  analyzing   the  data  in this  study  using  a linearity  test  and  simple  linear  regression analysis  the t test. The level of education  has an average  value of 18.60 with a maximum value  of24,   the minimum  value  of 14, a standard  deviation  of 2.523,   median  and mode 18.50 by 18. From  the description  of the variables  is known  that the level of education  of respondents  tended  to agree on the level of education  is used managers  (average  18.60), Quality  employees   have  an average  value  of 53.64  with  a maximum   value  of  75, the minimum  value of37,  a standard  deviation  of9.752,   55.00 median  and mode of 60. From the description   of the variable  quality  of employee   respondents   tended  to have  known that the quality  of work  (average  53.64). Linearity  test results note that the value of 0.937> FhitunFgtabel  at 4.03 and Sig linearity  of 0.000  < 0.05  mean education  level has an influ- ence on the quality of employees'  BPR POLATAMA KUSUMA  Madiun. Results of simple linear  regression  analysis  obtained   by the equation  Y = 43.696  + 0.535  X mean  when Level up 1% Quality Education employees will also rise by 0.535%, while other factors being equal. While the results of the calculation of the t test using SPSS for Windows 16.0 tcount obtained for 0.968 > 1.677 for mean Ha ttabel accepted and HO is rejected it means there is the influence of the educational level of the employees'  quality of BPR POLATAMA KUSUMA Madiun.